I will take a nap! - Willems, Mo. (New York : Hyperion Books for Children, 2015)
Gerald is tired and cranky and wants to take a nap, but Piggie is not helping.
Kirkus Review, April 2015.
1.2
K-3
190L
H
Keywords: Naps (Sleep) -- Fiction; Elephants -- Fiction; Pigs -- Fiction; Friendship -- Fiction; Sleep -- Fiction; Elephants -- Fiction; Readers (Elementary)